Characteristics of uterine leiomyoma patients at the Department of Obstetrics and Gynecology, Dr. Soetomo Hospital, Surabaya, from January to December 2014 - Listiana Rizka Pranandari; Hari Nugroho; Dwi Aprilawati (Universitas Airlangga, 2017)
Objectives: To study the characteristics of patient with uterine leiomyoma to be used as reference and evaluation.Materials and Methods: The data of this study taken by assess-ing patients’ medical record to be analyzed descriptively.Results: Of 145 patients, 69,7% were female who are older than forty years of age. Uterine leiomyoma often occur in patients of reproductive age (31%). Only 2.8% patient used oral contra-ceptive and 15.2% had menarche at the age of 12-13 years. The number of uterine leiomyoma was higher in female who had history of pregnancy less than or equal to two times (35.2%) and dominated by patients who had history of birth less than or equal to two times (37.2%). 63.4% patient never consume cigarette. Moreover, 29.7% of patients were overweight female. Unfortun-ately, there is no data about family history, exercise habit and history of tissue injury in the medical record.Conclusion: In this study, patients with uterine leiomyoma are dominantly female at age more than forty and at reproductive or perimenopause period with history of pregnancy and birth less than or equal to 2 times, never consume cigarette and overweight.